2006
DOI: 10.1074/jbc.m602074200
|View full text |Cite
|
Sign up to set email alerts
|

Heme Oxygenase-1 Protects Gastric Mucosal Cells against Non-steroidal Anti-inflammatory Drugs

Abstract: Gastric mucosal cell death by non-steroidal anti-inflammatory drugs (NSAIDs) is suggested to be involved in NSAID-Non-steroidal anti-inflammatory drugs (NSAIDs) 2 are a useful family of therapeutics, accounting for nearly 5% of all prescribed medications (1). The anti-inflammatory actions of NSAIDs are mediated through their inhibitory effects on cyclooxygenase (COX)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
66
0

Year Published

2007
2007
2024
2024

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 83 publications
(68 citation statements)
references
References 70 publications
2
66
0
Order By: Relevance
“…Local production of CO will be beneficial since the disturbance of gastric microcirculation is deeply implicated in the pathogenesis of AGML (16). Several lines of studies suggest that HO-1 prevents gastric and colonic damages (14,15). Metabolites of HO-1 also show protective effects against the gastro-intestinal lesions.…”
Section: Discussionmentioning
confidence: 99%
“…Local production of CO will be beneficial since the disturbance of gastric microcirculation is deeply implicated in the pathogenesis of AGML (16). Several lines of studies suggest that HO-1 prevents gastric and colonic damages (14,15). Metabolites of HO-1 also show protective effects against the gastro-intestinal lesions.…”
Section: Discussionmentioning
confidence: 99%
“…[30][31][32] However, it has been reported that NSAIDs induce necrosis and apoptosis in cultured gastric mucosal cells and in the gastric mucosa in a manner independent of COX inhibition, [33][34][35][36][37] and that the total inhibition of PG production in the stomach causes very little gastric damage in rats. 38) Therefore it is now believed that the inhibition of COX by NSAIDs is not the sole explanation for the gastrointestinal side effects of NSAIDs, 39) and it is assumed that other mechanisms in addition to PG deficiency are involved in the gastric ulcerogenicity of NSAIDs.…”
Section: Discussionmentioning
confidence: 99%
“…To test this hypothesis, we compared the gastrointestinal toxicity of indomethacin and 1 in C57BL6 mice. COX inhibition is believed to be a component of this undesired side effect of NSAIDs, but other possible mechanisms, including injury due to direct physical contact with the lining of the stomach, have been suggested (25). Thus, controversy surrounds the role of COX inhibition in the gastrointestinal toxicity of NSAIDs in general and indomethacin in particular.…”
mentioning
confidence: 99%